2018
DOI: 10.1094/pdis-12-17-1967-re
|View full text |Cite
|
Sign up to set email alerts
|

Neoscytalidium dimidiatum Causing Canker, Shoot Blight and Fruit Rot of Almond in California

Abstract: Almond trees with trunk and branch cankers were observed in several orchards across almond-producing counties in California. Symptoms of cankers included bark lesions, discoloration of xylem tissues, longitudinal wood necrosis, and extensive gumming. Spur and shoot blight associated with rotted fruit were detected in two orchards in Kern County. The fungus Neoscytalidium dimidiatum was consistently recovered from the various cankers, infected fruit, and blighted shoots and its identity was confirmed based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…The results obtained from the greenhouse experiment on young healthy plants after inoculation were similar to the disease symptoms on trees of royal poinciana located in the field, and that was confirmed by Koch's postulates when N. dimidiatum was frequently recovered from the inoculated seedlings. Our data match those in other trials using artificial inoculation of the same pathogen on royal poinciana [16] or other plant species [13][14][15]20,28]. Pathogenicity assays on seedlings of royal poinciana (Figure 4), F. benjamina and F. nitida [13] and eucalyptus, poplar and olive [30] clearly described that discoloration of vascular tissues, and drying and defoliation of leaves, were symptoms associated with stem canker caused by N. dimidiatum.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The results obtained from the greenhouse experiment on young healthy plants after inoculation were similar to the disease symptoms on trees of royal poinciana located in the field, and that was confirmed by Koch's postulates when N. dimidiatum was frequently recovered from the inoculated seedlings. Our data match those in other trials using artificial inoculation of the same pathogen on royal poinciana [16] or other plant species [13][14][15]20,28]. Pathogenicity assays on seedlings of royal poinciana (Figure 4), F. benjamina and F. nitida [13] and eucalyptus, poplar and olive [30] clearly described that discoloration of vascular tissues, and drying and defoliation of leaves, were symptoms associated with stem canker caused by N. dimidiatum.…”
Section: Discussionsupporting
confidence: 86%
“…In general, we noticed dieback, canker and gummosis, which ultimately led to complete dryness and death of royal poinciana trees (Figure 1). Although some studies have reported several fungi to cause cankers on plant species [5][6][7][8], others have recorded N. dimidiatum on almond, dragon fruit, eucalyptus, fig and plum, displaying disease symptoms of canker and dieback in different places of the world [13][14][15]28]. In general, environmental stress has negative impact on the severity of disease, depending on the level and duration of the stress, and the sensitivity and developmental stage of the plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neoscytalidium species have been related to stem canker, shoot blights and gummosis (Nouri, Lawrence, Yaghmour, Michailides, & Trouillas, ), and it has been described in plants such as Ficus carica , Hylocereus undatus , H. polyrhizus , Mangifera indica and root fruit (Nouri et al, ). The Eurotiales order, that includes Pencillium strains, was the second order with more isolates (13.3%) in this study.…”
Section: Discussionmentioning
confidence: 99%